Intestinal Infection of Candida albicans: Preventing the Formation of Biofilm by C. albicans and Protecting the Intestinal Epithelial Barrier - Peng, Ziyao; Tang, Jianguo (Frontiers in Microbiology, 2022)
The large mortality and morbidity rate of C. albicans infections is a crucial problem in medical mycology. Because the generation of biofilms and drug resistance are growing concerns, the growth of novel antifungal agents and the looking for newer objectives are necessary. In this review, inhibitors of C. albicans biofilm generation and molecular mechanisms of intestinal epithelial barrier protection are elucidated. Recent studies on various transcription elements; quorum-sensing molecules; host responses to adherence; and changes in efflux pumps, enzymes, bud to hyphal transition, and lipid profiles have increased the knowledge of the intricate mechanisms underlying biofilm resistance. In addition, the growth of novel biomaterials with anti-adhesive nature, natural products, drugs, bioactive compounds, proteins, lipids, and carbohydrates are being researched. Recently, more and more attention has been given to various metal nanoparticles that have also appeared as antibiofilm agents in C. albicans. The intestinal epithelial obstacle exerts an crucial effect on keeping intestinal homeostasis and is increasingly associated with various disorders associated with the intestine such as inflammatory bowel disease (IBD), irritable bowel syndrome, metabolic syndrome, allergies, hepatic inflammation, septic shock, etc. However, whether their involvement in the prevention of other intestinal disorders like IBD are useful in C. albicans remains unknown. Further studies must be carried out in order to validate their inhibition functions in intestinal C. albicans. This provides innovates ideas for intestinal C. albicans treatment.